1974
DOI: 10.1007/bf01221630
|View full text |Cite
|
Sign up to set email alerts
|

The effect of serotonin on in vitro insulin secretion and biosynthesis in mice

Abstract: Summary. The effect of serotonin on insulin secretion and biosynthesis was studied using isolated islets of mice. Serotonin produced a small stimulatory effect on insulin secretion when glucose was present in the incubation medium at a low concentration. On the other hand, an inhibition of insulin secretion was obtained with serotonin when glucose in the medium reached 3.0 mg/ml concentration. No significant effect of serotonin was obtained on insulin biosynthesis, neither in the presence of low nor with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
24
1
2

Year Published

1978
1978
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 17 publications
5
24
1
2
Order By: Relevance
“…In agreement with several previous studies (29,30), we observed that 5HT exerts profound acute and long lasting inhibitory effects on glucose-induced insulin secretion from perifused rat islets. It also abolished tolbutamide-induced secretion as well.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with several previous studies (29,30), we observed that 5HT exerts profound acute and long lasting inhibitory effects on glucose-induced insulin secretion from perifused rat islets. It also abolished tolbutamide-induced secretion as well.…”
supporting
confidence: 93%
“…Not all reports, however, agreed with this concept (28). Unfortunately in none of the electrophysiologic studies (21-26) was glucose-induced insulin secretion actually assessed to corroborate the amperometric analyses, and despite previous studies demonstrating an adverse effect of 5HT on insulin secretion (29,30), the possibility that 5HT preloading might negatively affect secretion was not examined in any of these amperometry studies.In an attempt to resolve the opposite concepts with regard to the inhibitory or stimulatory effects of insulin on ␤-cell secretion, we conducted studies with islets treated with 0.5 mM 5HT. In agreement with several previous studies (29, 30), we observed that 5HT exerts profound acute and long lasting inhibitory effects on glucose-induced insulin secretion from perifused rat islets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4), previously gassed with CO 2 /O 2 (5/95%), containing 1% B MAIZTEGUI and others . Islet glucokinase in insulin resistance (w/v) BSA and different glucose concentrations (2, 4, 8, 12, 16, and 20 mM;Gagliardino et al 1974). At the end of the incubation period, aliquots from the medium were taken to measure insulin by RIA (Herbert et al 1965).…”
Section: Insulin Secretion In Vitromentioning
confidence: 99%
“…Groups of five islets were incubated for 60 min at 37 C in 0·6 ml of Krebs-Ringer bicarbonate buffer, pH 7·4, previously gassed with CO 2 /O 2 (5%/95%), containing 1% (w/v) BSA and 3·3 or 16·7 mM glucose (Gagliardino et al 1974). At the end of the incubation period, aliquots were taken from the medium to measure insulin by RIA (Herbert et al 1965, Linde et al 1980.…”
Section: Insulin Secretion In Vitromentioning
confidence: 99%